Evaluation of possible hepatoprotective potentials of Parinari kerstingiimethanol stem bark extract and molecular docking of its compounds against CYP2E1 enzyme - Patrick Emeka Aba; anefavour Chiegeilo Akporeha
Liver diseases are becoming rampant due to the increasing number of hepatotoxicants, including drug abuse. Medicinal plants are known for their hepatoprotective properties. This study evaluated possible in vivo and in silico hepatoprotective potentials of Parinar kestingii extract. Thirty Wistar rats assigned to six groups (A-F) of five rats per group were used to investigate in vivo hepatoprotective effects. Rats in groups A and B were pretreated with distilled water, while groups C, D, E and F rats received 200, 400, and 600 mg/kg of the extract and 100 mg/kg of silymarin, respectively, as pretreatments. All pretreatments lasted for 14 days, and on day 15, acetaminophen (2000 mg/kg) was administered to all the rats except those in group A. Forty-eight hours after, sera samples for assay of biochemical parameters (ALT, AST, ALT Bilirubin) were obtained, and the liver was harvested for histopathology studies. Gas chromatography-mass spectrometry was used to separate and identify the compounds present. Molecular docking on Butylated hydroxytoluene, Indazole, 4-methyl pyrazole and CYP2E1 was performed using Autodock Vina. The mean ALT, AST, and ALP activities of the extract-treated rats were significantly lower than that of group B but were comparable with those of groups A and F. Hepatocytes of the extract-treated showed less severe lesions compared to those of the negative control. Gas chromatography-mass spectrometry results indicated various compounds in the extract. The binding affinities (kcal/mol) between CYP2E1 and the ligands butylated hydroxytoluene, indazole, and 4-methyl pyrazole were -6.7, -5.1, and -3.8, respectively. It was concluded that the extract possesses both in vivo and in silico hepatoprotective abilities.